Modelling the Human Cardiac Fluid Mechanics. 4th ed - Oertel, HerbertKrittian, Sebastian (KIT Scientific Publishing, 2012)
With the Karlsruhe Heart Model (KaHMo) we aim to share our vision of integrated computational simulation across multiple disciplines of cardiovascular research, and emphasis yet again the importance of Modelling the Human Cardiac Fluid Mechanics within the framework of the international STICH study. The focus of this work is on integrated cardiovascular fluid mechanics, and the potential benefits to future cardiovascular research and the wider bio-medical community.